1987
DOI: 10.1152/jappl.1987.62.5.1907
|View full text |Cite
|
Sign up to set email alerts
|

Temperature alters bronchial blood flow response to pulmonary arterial obstruction

Abstract: Lobar bronchial blood flow has been reported to increase and decrease acutely after pulmonary arterial obstruction (PAO). Because bronchial blood flow (Qbr) to the trachea and bronchi is influenced by inspired air temperature, we investigated whether temperature differences could explain these disparate results. In 10 open-chested dogs the left lower lobe (LLL) was isolated and perfused in situ with autologous blood at a controlled temperature with an independent vascular circuit. The abdomen and the chest of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, these investigations utilized a preparation in which measurement of bronchial blood flow necessitated either unilateral pulmonary artery occlusion [8] or the absence of pul monary blood flow [7,15], both of which could by themselves affect bronchial blood How [4,14]. In the current study we confirmed that Qbr(s-p) is reduced by PEEP and that this effect was observed when pul monary blood flow was intact.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, these investigations utilized a preparation in which measurement of bronchial blood flow necessitated either unilateral pulmonary artery occlusion [8] or the absence of pul monary blood flow [7,15], both of which could by themselves affect bronchial blood How [4,14]. In the current study we confirmed that Qbr(s-p) is reduced by PEEP and that this effect was observed when pul monary blood flow was intact.…”
Section: Discussionsupporting
confidence: 76%
“…Qbr(s-p) to the LLL was measured according to a technique pre viously described [4,6]. The only flow of blood into the closed vas cular circuit of the LLL is from the bronchial vessels which anasto mose with the pulmonary circulation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The partitioning between right and left drainage of bronchial blood flow is not influenced by the presence or absence (as it happens during total cardiopulmonary bypass) of pulmonary circulation . 21 Our technique for measuring Qbr(s-p) was derived from a technique utilized in studies of dogs. 12 • 21 In animal studies, the possible accumulation or loss of blood into the lungs is evaluated when calculating Qbr(s-p) by adding to the measured blood flow the lung weight changes.…”
Section: Discussionmentioning
confidence: 99%